PARADIGM OF SOCIAL FACTS AND EDUCATION ON SOCIAL REALITY - Heny Suhindarno; Yosep Heristyo Endro Baruno (International Journal of Teaching and Learning, 2024)
Educational activities are a social reality in society. As a unit of activity, education is influenced by and influences the components of society. The increasing demands of society for education and advances in science and technology have made it no longer possible for education to be managed solely through traditional patterns, in addition to this method no longer being in accordance with the needs and demands of society. The revolution in technology and science, changes in society, understanding of how children learn, advances in communication media, and so on give their own meaning to educational activities and this is what makes the policy of utilizing technological media and technological approaches in managing education as part of culture a means of transmitting values and ideas, so that everyone is able to participate in the transformation of values for the progress of the nation and state. The reality of education in society is still shackled by policy and control by the hands of power, the political elite. As a capitalist system of color, the policy changes made still cannot answer social problems.